Current pattern of secondary glaucoma - Sherpa, Dakki; Pokhrel, Suprada (Journal of Chitwan Medical College, 2017)
Objective: To determine the pattern of secondary glaucoma in Nepal Eye Hospital. Material and Methods: A retrospective hospital based analysis of medical records of patients attending Nepal Eye Hospital Glaucoma clinic over a period of 1 years (Jan 2013 - Jan 2014) was done in order to know the pattern of secondary glaucoma to launch a preventive measure to decrease the burden of glaucoma blindness. Results: A total of 59 patients with secondary glaucoma were seen during a period of one year. Out of 59 patients of secondary glaucoma 35 (59.28%) were male and 24 (40.66%) were female with male and female ratio to be 1.46:1. Neovascular glaucoma comprised of 52.54%, Lens induced glaucoma 20.34%, Uveitic glaucoma 8.4%, Pseudoexfoliation syndrome 6.75%, Angle recession glaucoma 3.39%, Steroid induced glaucoma 3.39%, Pigmentary glaucoma 1.69%, Pseudophakic glaucoma 1.69% and Glaucomatoiridocyclitic crisis 1.69%. A large number of patients had profound loss of vision and 81.35% patients had presenting visual acuity of less than 3/60. Conclusion: Secondary glaucoma is a significant problem due to its impact on visual acuity. Identification of etiology of secondary glaucoma along with preventive measures must be undertaken to decrease this burden of blindness in Nepal.